Environmental Color and the Cooperative Behavior of Children with Sensory Processing Challenges: An Exploratory Study - Read,Marilyn (Creative Education, 2019)
The difficult challenge faced by occupational therapists and preschool teachers today is creating environments that benefit concurrently the behaviors of all children within one classroom setting. Occupational therapists and teachers design both the physical environment and the social environment for children with developmental needs across a broad spectrum of abilities. Children who have atypical reactions to sensory stimuli may benefit from a space with environmental color because it could act as a modifier for their attention in the environment. The purpose of this study was to investigate the impact of environmental color on the cooperative behavior of preschool children assessed with having one or more sensory processing challenges. It was predicted that walls with environmental color from focal colors (purple, blue, green, yellow, orange, and red) would positively impact the overall cooperative behavior of children with sensory processing challenges relative to a wall of white color scheme. The male participant showed higher cooperation scores in all visible-spectrum focal color conditions compared to the white color conditions. The cooperation scores for the female participant were lower on all visible-spectrum focal color conditions, except for orange, as compared with the white conditions. The results of the two different case studies within the environmental conditions are illustrated with discussion and implications of the research findings.
Keywords: Design Program